178k views
2 votes
The steps to derive the quadratic formula are shown below:

Step 1 ax2 + bx + c = 0
Step 2 ax2 + bx = − c
Step 3 x2 + b over a times x equals negative c over a
Step 4 Blank space, fill in the answer
Provide the next step to derive the quadratic formula.
Answer Choices: (see image)

The steps to derive the quadratic formula are shown below: Step 1 ax2 + bx + c = 0 Step-example-1
User Yuuu
by
5.2k points

2 Answers

1 vote

Answer:

B

Explanation:

User Raed Alahmad
by
5.3k points
6 votes

Answer:

b)


x^(2) +(b)/(a) x+((b)/(2 a) )^(2) = (-c)/(a) + ((b)/(2 a)) ^(2)

Explanation:

Step(i):-

Given quadratic equation ax² + bx + c = 0

step(ii):-

ax² + bx = -c

Step(iii):-

Dividing 'a' on both sides , we get


(ax^(2) +bx )/(a) = (-c)/(a)


x^(2) + (bx)/(a) = (-c)/(a)

Step(iv):-

Adding
((b)/(2 a) )^(2) on both sides , we get


x^(2) +(b)/(a) x+((b)/(2 a) )^(2) = (-c)/(a) + ((b)/(2 a)) ^(2)

User IKK
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.